Firm’s Growth and Share Price Volatility: Evidence from Pakistan - Ataullah; Nishad Hussain; Muhammad Tahir Khan (UW Journal of Management Sciences, 2023)
Purpose: This research aims to determine how the growth of non-financial dividend-paying companies affects stock prices. This study investigates the impact of growth of the firm on stock prices using different statistical tools and models. Design and Methodology: A decade of research will be conducted from 2011 to 2020. Dividend announcements, gearing ratios, firm size, and profitability ratios—all growth indicators—are significant drivers of stock price volatility, according to the findings of this study. Findings: The results support Lintner's and Gorden's "Bird in Hand theory". Companies can earn the trust of long-term investors by maintaining a consistent dividend policy and growth rate. Investors may find more excellent value in the stocks of companies that consistently report significant dividend increases and have a high profitability ratio. Companies that announce high dividends, gearing ratios, and profits typically have promising futures and rising earnings. The study's findings suggest that, from a shareholder's standpoint, shareholders should prefer stocks of companies that pay a high and stable dividend, are large, and generate significant profits. Implications: Findings are providing information to investors that companies' stock prices are so sensitive to dividend volatility and low profitability ratios because these factors directly impact those metrics.